2012
DOI: 10.1007/s00775-012-0889-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reactivity on cellular accumulation and cytotoxicity of oxaliplatin analogues

Abstract: The purpose of this study was to systematically investigate the relationships between reactivity, cellular accumulation, and cytotoxicity of a panel of oxaliplatin analogues with different leaving groups in human carcinoma cells. The reactivity of the complexes towards the nucleotides 2'-deoxyguanosine 5'-monophosphate and 2'-deoxyadenosine 5'-monophosphate was studied using capillary electrophoresis. Cellular accumulation and cytotoxicity were measured in an oxaliplatin-sensitive and oxaliplatin-resistant ile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 41 publications
5
27
0
Order By: Relevance
“…In RPMI medium, which is used routinely for mammalian tissue culture, slow activation of 1 by the nucleophiles present in the medium was observed (Figure S19). This result is consistent with the previously reported activation of structurally similar platinum compounds by nucleophiles ,. No significant decomposition was noticed up to 8 h, and approximately 60 % of 1 remained unchanged even after 24 h, suggesting that the compound is highly stable in biological media.…”
Section: Figuresupporting
confidence: 93%
“…In RPMI medium, which is used routinely for mammalian tissue culture, slow activation of 1 by the nucleophiles present in the medium was observed (Figure S19). This result is consistent with the previously reported activation of structurally similar platinum compounds by nucleophiles ,. No significant decomposition was noticed up to 8 h, and approximately 60 % of 1 remained unchanged even after 24 h, suggesting that the compound is highly stable in biological media.…”
Section: Figuresupporting
confidence: 93%
“…Reduced cisplatin accumulation in A2780cis cells compared to the parent sensitive cell line is well-documented [ 36 ]. According to our earlier results, HCT-8 colorectal cancer cells accumulated significantly less cisplatin than A2780 ovarian cancer cells after 2 h incubation with 100 ”M platinum drug (HCT-8: 10.47 ± 0.88 ng Pt/10 6 cells, mean ± SEM, n = 6, [ 37 ]; A2780: 17.68 ± 0.23 ng Pt/10 6 cells, mean ± SEM, n = 3, [ 38 ]; p < 0.001, unpaired t -test). Nevertheless, the fate of the drug in cytosol is also of great importance.…”
Section: Discussionmentioning
confidence: 90%
“…[14] Indeed we observed that 1 is highly stable in water as evidenced by no change in the 1 HNMR spectrum of 1 after 72 hi nD 2 O( Figure S18). [14] Indeed we observed that 1 is highly stable in water as evidenced by no change in the 1 HNMR spectrum of 1 after 72 hi nD 2 O( Figure S18).…”
mentioning
confidence: 86%